Pengaruh Daya Tarik Dan Intensitas Penayangan Iklan Terhadap Citra Merek Dan Dampaknya Pada Keputusan Pembelian Konsumen Produk Sabun Lifebouy Pada PT. Trans Retail Carrefour - Triputra, Jihad; Batubara, Maisara (Universitas Harapan Medan, 2025)
This study aims to determine whether the attractiveness of advertisements and the intensity of ad serving partially affect the brand image. To determine whether the attractiveness of advertisements, the intensity of ad serving and brand image partially influence the purchasing decisions of consumers. This is to find out whether the brand image mediates the relationship between the attractiveness of advertisements and the intensity of advertising on the purchasing decisions of consumers. The total population in this study was 260 people, and by using the Non Probability Sampling technique used, namely by using the purposive sampling method. The analysis technique used is path analysis. The results showed that the attractiveness of advertising had a significant effect on brand image, the intensity of ad serving had no significant effect on brand image, the attractiveness of advertisements had a significant effect on consumer purchasing decisions, the intensity of ad serving had a significant effect on consumer purchasing decisions for Lifebouy soap products, brand image. There is no significant effect on consumer purchasing decisions, there is no significant effect on the attractiveness of advertising on consumer purchasing decisions through brand image and there is no significant effect on the intensity of ad serving on consumer purchasing decisions for Lifebouy soap products through brand image.